1972
DOI: 10.1073/pnas.69.12.3713
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Plastoquinone Analogs and Inhibition of Photosynthetic and Mammalian Enzyme Systems

Abstract: New 5-hydroxy-and 5-chloro-6-alkyl-1,4-benzoquinones with one or two methyl groups on the nucleus were synthesized as potential antimetabolites of plastoquinones for biological research on photosynthetic and mammalian enzyme systems; the primary emphasis was on photosynthesis.2,3-Dimethyl-5 -hydroxy -6 -phytyl -1,4 -benzoquinone completely inhibited in chloroplasts the water-dependent electron transport, but photosystem I was insensitive to this analog. The data are consistent with the interpretation that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Regarding uses of important drugs for the treatment of cancer, mitomycin C, mitoxantrone, and doxorubicin draw attention and contain the 1,4-quinone moiety ( Figure 2 ). After realizing the prominent anticancer activity of those structures, we created more using nature as a model, namely plastoquinones ( PQ ) discovered by Barr for electron transfer in photosynthesis in 1946 [ 24 ] containing both 2,3-dimethyl-1,4-benzoquinone structure and a side chain of nine isoprenyl group as PQ-A or PQ-9 [ 25 ] or shorter side chain such as PQ-3 with three isoprenyl side units, as shown in Figure 3 [ 26 ]. Studying common pharmacophoric features of PQ analogs has revealed that the presence of three main features, as shown in Figure 3 , are important.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding uses of important drugs for the treatment of cancer, mitomycin C, mitoxantrone, and doxorubicin draw attention and contain the 1,4-quinone moiety ( Figure 2 ). After realizing the prominent anticancer activity of those structures, we created more using nature as a model, namely plastoquinones ( PQ ) discovered by Barr for electron transfer in photosynthesis in 1946 [ 24 ] containing both 2,3-dimethyl-1,4-benzoquinone structure and a side chain of nine isoprenyl group as PQ-A or PQ-9 [ 25 ] or shorter side chain such as PQ-3 with three isoprenyl side units, as shown in Figure 3 [ 26 ]. Studying common pharmacophoric features of PQ analogs has revealed that the presence of three main features, as shown in Figure 3 , are important.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs such as mitomycin C, mitoxantrone, and doxorubicin and some of the biologically active synthetic molecules contain 1,4-quinone moiety. Our strategy was inspired by a natural 2,3-dimethyl-1,4-benzoquinone structure with a side chain of nine isoprenyl groups named PQ-A or PQ-9 [ 30 ], as well as those containing shorter side chains such as PQ-3, having three isoprenyl side units as shown in Figure 1 [ 31 ]. In the past three years, we have published the syntheses and extensive exploration of a broad range of various PQ analogs to elucidate their antiproliferative and/or antibiotic profiles using 2,3-di-methylhydroquinone as a precursor [ 21 , 23 , 26 , 28 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%